Evaluating the usability expressiveness of a USability- oriented INteraction and Navigation model - Marques, Anna Beatriz Marques; Junqueira, Simone Diniz Junqueira; Conte, Tayana Conte; Keywords, ACM Classification Keywords (Teste, 2019)
The success of an interactive system is strongly related not only to the quality of its user interface, but also to the quality of its interaction and navigation mechanisms. Those mechanisms need to be carefully designed, but there are still no de facto standard design models to represent user-system interaction in a way that privileges decisions regarding the usability of the product being developed. Recently, we proposed USINN (USability-oriented INteraction and Navigation model) to express usability mechanisms in interaction and navigation modeling solutions. In this paper, we present an empirical study conducted in academic environment to investigate the use of USINN to represent usability mechanisms in interaction and navigation design solutions. The results indicated that the participants consider USINN to be easy to use and useful for the interaction and interface design. They also pointed out the need for a better knowledge about usability to apply USINN effectively.